Könnun á notkun magasárslyfja meðal Íslendinga - Hildur Thors; Helgi Sigurðsson; Einar Oddsson; Bjarni Þjóðleifsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Drugs for peptic ulcer (ACT class A02B) are extensively used in Iceland, 20 DDD/1000/day, which is 2-3 times higher than in other Scandinavian countries. A prescription survey was carried out during one month in 1991 with the help of pharmacists who registered all prescriptions with regard to age and sex of the patient, the speciality of the prescribing doctor and name, dose and quantity of the drug. A total of 2021 prescriptions were registered accounting for around 90% of all prescriptions. The prevalence of peptic ulcer drug use was 1.52% and maximal usage was in the age group 70-79, 2.91%. H2 blockers accounted for 79%, omeprazole for 17%, and other drugs for 4%. General practitioners prescribe 65% of the drugs, gastroenterologists 15% and other specialists 14%. If the patient himself collected the drug he was asked to fill out a questionnaire with regard to the reason for the prescription, previous prescriptions and investigations. A total of 1131 (56%) questionnaires were received. Only 1% of the patients did not know the reason for the prescription. The patients registered that 30% of the prescriptions were for peptic ulcer, 29% for heartburn, 21% for gastritis, 9% for dyspepsia and 7% for prevention of side effects of other drugs. Investigations were done in 67% of the patients, but 33% received prescription after doctor's interview only. It was estimated from the data that about 40% of the prescriptions were for non-ulcer dyspepsia. The results suggest that the extensive use of peptic ulcer drugs in Iceland is due to excessive use in non-ulcer dyspepsia. Notkun lyfja við sársjúkdómi í meltingarfærum er nú um 20 DDD/1000 íbúa/dag, sem er tvisvar til þrisvar sinnum meira en á hinum Norðurlöndunum. Tilgangur þessarar rannsóknar var að kanna hvernig íslenskir læknar ávísa magalyfjum og hugsanlega að finna ástæður fyrir þessari miklu notkun. Lyfseðlar á magasárslyf (ATC flokkur A02B) í aprílmánuði 1991 voru ...